Criteria for Ideal Leaders in the Texts of Hikayat Raja dan Sultan: Intertextuality Study Julia Kristeva - Hanifah Yulia Sari; Diantri Seprina Putri; Vivi Indriyani; Lintang Nurlisya Putri; M. Raphi Parhan Butar-Butar; Fitriani (Raja Zulkarnain Education Foundation, 2026)
Intertextuality is often interpreted as an attempt to compare two texts that are perceived as overlapping. In fact, the main purpose of intertextuality is to find the ideology contained within a text. This study uses the text of the Hikayat Raja dan Sultan as the main object. The research method uses philological research methods, considering that the text is a manuscript. The purpose of this study was to find the ideology of the Hikayat Raja dan Sultan manuscript. The results, the ideology in the text is visible from the transformation process of the Tajussalatin text. The difference in genre is quite significant, the Tajussalatin text belongs to the literary genre of books, while the Hikayat Raja dan Sultan text belongs to the genre of Sufism texts. In addition, based on the ideology shows the legitimacy of the